Quantitative Genetics of Smoltification Status at the Time of Seawater Transfer in Atlantic Salmon (Salmo Salar) - Khaw, Hooi Ling; Gjerde, Bjarne; Boison, Solomon A.; Hjelle, Elise; Difford, Gareth F. (Frontiers in Genetics, 2021)
High mortality during grow-out in the sea is a challenge for farmed Atlantic salmon production in Norway and globally, which is partly attributed to sub-optimal smolt quality. In this study two groups of pre-smolts were put on a standard light smoltification regime with alternating 12L:12D per day for six weeks (Phase I), followed by 24L:0D per day for six weeks (Phase II); one group was 0+ smolt (EXP1) and the other to become 1+ smolt (EXP2). For monitoring the smoltification status of the fish, 100 (EXP1) and 60 (EXP2) fish were randomly sampled per week during Phase II. The following phenotypes for smoltification status were studied; RT-qPCR relative expression of two variants of the Na+K+ATPase alpha subunits in the gills, Alpha1a with increased expression in freshwater (FW) and the alpha1b with increased expression in seawater (SW), and their ratio SW/FW. At the optimal time for seawater transfer based on the SW/FW trait, 1000 (at sixth sampling of EXP1) and 1500 (at fifth sampling of EXP2) fish were sampled for genetic parameter estimation. The individual variation in FW, SW and SW/FW was very large at each of the seven samplings indicating large variation among individual in the optimum time of transfer to seawater. SW/FW showed significant genetic variation in both 0+ and 1+ smolts, which indicates the possibility for selection for improved synchronization of smoltification status of Atlantic salmon at the time where the largest proportion of the fish are considered to be smolt. However, the genetic correlation between SW/FW of 0+ and 1+ was not significantly different from zero indicating very little shared genetic variation in SW/FW in 0+ and 1+ fish. Smoltification phenotypes showed temporal progression over the smoltification period and this progression varied between 0+ and 1+ smolt highlighting the importance of correctly timing the major sampling point and cohorts are transferred to seawater. This also highlighted the need for further research into non-invasive methods of objectively measuring individual smoltification through time and subsequent smolt survival and growth rate at sea.